Nutritional Composition and Health Benefits of Various Botanical Types of Melon (Cucumis melo L.) - Shivapriya Manchali; Kotamballi N. Chidambara Murthy; Vishnuvardana; Bhimanagouda S. Patil (Plants, 2021)
Characterizing the diverse melon cultivars for nutrition aids in crop improvement and promoting a healthy diet. Here, we used in vitro assays to characterize the nutritional qualities and health-beneficial effects of 30 melon (Cucumis melo L.) genotypes, including 10 improved cultivars, 16 landraces, and 4 wild types collected from different parts of India. Two landraces (Sidoota and Alper Green) had the highest (12.20 and 11.25) total soluble solids (TSS) contents. The Sidoota and Pappusa landraces had high reducing sugar contents (2.84 and 2.81 mg g−1 fresh weight [FW]). The highest polyphenols contents (22.0 mg g−1 FW) were observed in the landraces Mage Kaayi-2, Budamekaayi, and Small Melon. Reflecting on the primary and secondary metabolite contents, the Mekke Kaayi and Giriyala landraces exhibited high 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity (97.6 and 91% at 100 μg mL−1). Additionally, seven of the landraces showed significant nitric oxide (NO) induction activity (>80% inhibition at 200 μg mL−1), indicating their potential health benefits, and seven showed considerable angiotensin-converting enzyme (ACE) inhibition activity (highest in Kashi Madhu), indicating their potential usefulness in reducing hypertension. Genotypes with high health beneficial compounds identified in this study can be used for breeding improved melon cultivars to promote these fruits as well as a healthy diet.